Vermeidung postoperativer Infektionen: evidenzbasierte Prinzipien - Pianka, Frank; Mihaljevic, André Leopold (Der Chirurg, 2017)
BackgroundSurgical site infections (SSI) are one of the most frequent postoperative complications worldwide and preventive measures are still an important research topic. High infection rates are not uncommon, especially in visceral surgery. At the same time, frequently not all evidence-based measures are carried out in a standardized manner. The aim of this article is to summarize the relevant literature on evidence-based measures for prevention of SSI. Although evidence-based medicine has already become well-established in surgery, the opinion of experts often still prevails.Material and methodsThe current literature on preventive measures and recommendations was reviewed and the results are appraised.ResultsMany different preventive measures could be identified in the literature, which can be classified into preoperative, intraoperative and postoperative measures. Recommendations for implementation of individual measures are made depending on the underlying evidence.ConclusionThe occurrence of SSI can effectively be reduced by adhering to evidence-based principles.
Gesehen am 27.09.2018